Electret

CN120934372APending Publication Date: 2025-11-11DENSO CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510551626.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-05-08
Filing Date
2025-04-29
Publication Date
2025-11-11

AI Technical Summary

Technical Problem

Existing electret materials have difficulty maintaining a high surface potential for a long time in high-temperature environments, and their thermal stability and time stability are insufficient, which affects their application in high-temperature environments.

Method used

The structure consists of an outer film and an inner film. The outer film is a composite metal oxide with a band gap energy of 3eV or higher, while the inner film is made of different materials. An electret layer is formed by charging. The outer film exhibits a high potential, while the inner film suppresses charge loss and maintains a stable potential.

Benefits of technology

It can maintain a high surface potential even at high temperatures, which improves the thermal and time-dependent stability of the electret, making it suitable for high-temperature processes and cost reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120934372A_ABST
    Figure CN120934372A_ABST
Patent Text Reader

Abstract

An electret (1) has a substrate (10) and an electret layer (2) formed on the surface of the substrate (10), the electret layer (2) being obtained by electrically charging an inorganic dielectric film (20) including an outer layer film (3) and an inner layer film (4) laminated in the thickness direction (X) of the substrate (10), the outer layer film (3) being a film mainly composed of a first inorganic dielectric material, and the inner layer film (4) being a film mainly composed of a second inorganic dielectric material. The first inorganic dielectric material is a composite metal compound containing two or more different metal elements, contains at least a trivalent metal element, and has a band gap energy of 3 eV or more, and the inner layer film (4) is a film having a second inorganic dielectric material different from the first inorganic dielectric material as a main component.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to electrets. Background Technology

[0002] Electrets are charged materials that provide an electrostatic field to their surroundings and have historically been used in applications such as electret condenser microphones and dust filters. Furthermore, in recent years, their application in vibration power generation, a type of energy harvesting technology, has been anticipated. For example, the practical application of small vibration power generation components using electrets is expected as integrated circuit embedded components used in electrostatic vibration generators driven by environmental vibrations.

[0003] As constituent materials for electrets, organic polymers such as fluorinated resins are generally used. Organic polymers offer excellent freedom in shape and control over film thickness during film formation. However, due to potential thermal instability of surface potential and performance degradation over time, research is underway to develop inorganic compound materials with superior thermal stability. Examples of known inorganic compound materials include electrets using sintered hydroxyapatite bulk bodies and electrets using composite oxides with perovskite structures.

[0004] Furthermore, power generation devices using inorganic electrets, when assembled onto integrated circuits formed on a substrate, can achieve miniaturization and operation in high-temperature environments, and are expected to be used in various applications. Therefore, the inventors of this application previously proposed an electret having a substrate and an electret layer formed on its surface, wherein a thin film mainly composed of an inorganic dielectric material is used in the electret layer. This inorganic dielectric material is a composite metal compound containing two or more different metal elements, and its band gap energy is 4 eV or higher (Patent Document 1).

[0005] Existing technical documents

[0006] Patent documents

[0007] Patent Document 1: Japanese Patent No. 7390687 Summary of the Invention

[0008] The electret described in Patent Document 1 is considered to control defects by giving the inorganic dielectric material containing two or more metallic elements a high band gap energy, and it can undergo high-voltage polarization treatment at high temperatures, exhibiting a high surface potential. Therefore, a relatively stable surface potential can be obtained in temperature environments above room temperature (e.g., around 100°C), but it is difficult to maintain the high surface potential immediately after electretization. In particular, in high-temperature environments exceeding 100°C (e.g., above 200°C), it has been found that the surface potential tends to disappear over time, and there is a need to improve its long-term stability.

[0009] In addition, electrets are known to be thin films or combinations of conventional inorganic compound materials or fluorine-based organic polymer materials formed on a substrate. However, conventional inorganic compound materials used in device formation cannot achieve high surface potentials, and although fluorine-based organic polymer materials exhibit relatively high surface potentials at room temperature, their heat resistance is low, making them difficult to apply to devices used in high-temperature environments.

[0010] The present invention was made in view of such a problem, and the object is to provide an electret that can maintain a high surface potential for a long time even in high temperature environments, and has excellent thermal stability and time stability.

[0011] One aspect of the present invention is an electret having a substrate and an electret layer formed on its surface. The electret layer is obtained by subjecting an inorganic dielectric film comprising an outer layer film and an inner layer film stacked in the thickness direction of the substrate to an electric charge. The outer layer film is a film with a first inorganic dielectric material as its main component. The first inorganic dielectric material is a composite metal compound containing two or more different metal elements, and contains at least a trivalent metal element. The band gap energy of the first inorganic dielectric material is 3 eV or higher. The inner layer film is a film with a second inorganic dielectric material, different from the first inorganic dielectric material, as its main component.

[0012] In structures where an electret layer is disposed on a substrate, under high-temperature conditions, charge tends to move from the surface in contact with the substrate, which can be expected to lead to a decrease in surface potential. In contrast, the electret in this method has a stacked structure including an outer layer and an inner layer, thereby maintaining a stable high surface potential even under high-temperature conditions. The reason for this is not necessarily clear, but it is speculated that the outer layer, consisting of a first inorganic dielectric material and composed of a specific composite metal oxide with a band gap energy of 3 eV or higher, which exhibits a high surface potential through charging treatment, is disposed on the outside of the electret layer, while the inner layer, consisting of a second inorganic dielectric material, is disposed on the inside of the outer layer. This results in a higher charge storage effect at the stacked interface area and suppresses charge outflow to the substrate.

[0013] As a result, the accumulated charge can be stably maintained, and surface potential changes can be suppressed regardless of the temperature environment. Therefore, the electret maintains its initially high surface potential and exhibits stable performance even in harsh environments. Furthermore, in the manufacture of power generation devices using electrets, high-temperature processes can be applied, increasing design freedom and contributing to reduced manufacturing costs.

[0014] As described above, the above method can provide an electret that can maintain a high surface potential, excellent thermal stability, and excellent stability over time even in high-temperature environments. Attached Figure Description

[0015] Figure 1 This is a schematic diagram showing the general structure of the electret in Embodiment 1.

[0016] Figure 2 This is a schematic diagram showing a structural example of the electret in Embodiment 1.

[0017] Figure 3 This is a schematic diagram showing a structural example of the electret in Embodiment 2.

[0018] Figure 4 This is a schematic diagram showing the general structure of the electret of the comparative example and a graph showing the relationship between heat treatment and surface potential.

[0019] Figure 5 This is a graph showing the relationship between the thickness of the inner layer film of the electret in the embodiment and the surface potential.

[0020] Figure 6 This is a graph showing the relationship between time and surface potential after the charged treatment in the embodiment.

[0021] Figure 7 This is a graph showing the relationship between the thickness of the outer layer of the electret and the surface potential in the embodiment.

[0022] Figure 8 This is a graph showing the relationship between time and surface potential after the charged treatment in the embodiment.

[0023] Figure 9 This is a graph showing the relationship between the thickness of the inner layer film of the electret in the embodiment and the surface potential.

[0024] Figure 10 This is a graph showing the relationship between time and surface potential after the charged treatment in the embodiment.

[0025] Figure 11 This is a graph showing the relationship between the thickness of the inner layer film of the electret in the embodiment and the surface potential.

[0026] Figure 12 This is a graph showing the relationship between the thickness of the inner layer film of the electret in the embodiment and the surface potential.

[0027] Figure 13 This is a graph showing the relationship between time and surface potential after the charged treatment in the embodiment.

[0028] Figure 14This is a graph showing the relationship between time and surface potential after the charged treatment in the embodiment.

[0029] Figure 15 This is a schematic diagram showing the approximate structure of the electret in the comparative example.

[0030] Figure 16 This is a graph showing the relationship between time and surface potential after the charge treatment of the comparative example.

[0031] Figure 17 This is a graph showing the relationship between time and surface potential after the charge treatment of the comparative example.

[0032] Figure 18 This is a graph showing the relationship between time and surface potential after electrification treatment in the embodiments and comparative examples.

[0033] Figure 19 This is a graph showing the relationship between time and surface potential after electrification treatment in the embodiments and comparative examples. Detailed Implementation

[0034] (Implementation Method 1)

[0035] Embodiment 1 of the electret will be described with reference to the accompanying drawings. Figure 1 As shown, the electret 1 of this embodiment includes a substrate 10 and an electret layer 2 formed on its surface. The electret layer 2 is formed by electretizing an inorganic dielectric film 20 through an electrical treatment. The inorganic dielectric film 20 includes an outer layer film 3 and an inner layer film 4 stacked in the thickness direction X of the substrate 10. The outer layer film 3 is a film mainly composed of a first inorganic dielectric material, and the inner layer film 4 is composed of a film mainly composed of a second inorganic dielectric material.

[0036] In the inorganic dielectric film 20, the outer layer film 3 is located outside the thickness direction X (i.e., the lamination direction) of the substrate 10, and the inner layer film 4 is located inside it. The first inorganic dielectric material, which is the main component of the outer layer film 3, is a composite metal compound containing two or more different metal elements, and can be selected from inorganic dielectric materials that contain at least a trivalent metal element and have a band gap energy of 3 eV or more. The second inorganic dielectric material, which is the main component of the inner layer film 4, can be selected from inorganic dielectric materials that are different from the first inorganic dielectric material.

[0037] The inorganic dielectric film 20 can exhibit desired electret characteristics by appropriately setting the combination of inorganic dielectric materials, film thicknesses, and electret conditions used to form the outer and inner layers 3 and 4. Furthermore, in the composition of the outer and inner layers 3 and 4, "main component" refers to materials that can be composed solely of the first and second inorganic dielectric materials, or may include impurities arising from the raw materials of the first and second inorganic dielectric materials, or may include other components added during the film formation process of the first and second inorganic dielectric materials.

[0038] Electret 1 is a charged material that provides an electrostatic field to its surroundings by maintaining a positive or negative charge on its surface. It exhibits electret properties by subjecting an inorganic dielectric film 20 formed on a substrate 10 to an electret process, thus becoming an electret layer 2. "Electretization" in other words refers to becoming a charged material by performing an electret process to make its surface potential apparent. Such an electret 1 can be used as an integrated circuit-embedded power generation element in various devices that convert mechanical energy into electrical energy, such as small electrostatic vibration power generation devices powered by environmental vibrations.

[0039] The first inorganic dielectric material constituting the outer film 3 can be any composite metal compound material containing two or more different metallic elements, including a trivalent metal element, and having a band gap energy of 3 eV or higher; its composition is not particularly limited. In this case, desired physical properties can be obtained based on the combination of the two or more metallic elements or the structure of the composition containing them. By having a relatively large band gap energy of 3 eV or higher, preferably 4 eV or higher, the insulation breakdown voltage increases. Therefore, a high voltage can be applied during charged processing, and the desired high surface potential can be exhibited. As the first inorganic dielectric material, a material with a band gap energy of 4.5 eV or higher is preferred, and a material with a band gap energy of 5.5 eV or higher is more preferred.

[0040] In this embodiment, the electret layer 2 has a structure in which an inner layer film 4 and an outer layer film 3 are sequentially stacked on the substrate 10. Since the outer layer film 3 is made of a first inorganic dielectric material with a relatively large band gap energy, a high surface potential can be exhibited. Furthermore, by placing the inner layer film 4, which uses a second inorganic dielectric material, inside the outer layer film 3, a charge storage effect at the layer interface can be achieved. The charge storage effect at the interface of such a stacked structure is known as the Maxwell-Wagner effect, but the combination of the outer layer film 3 using the first inorganic dielectric material and the inner layer film 4 using the second inorganic dielectric material exhibits a higher effect than previously seen in maintaining and stabilizing the amount of charge exhibited on the surface of the outer layer film 3.

[0041] It has been determined that, through such a structure, electret 1 maintains approximately the initial surface potential before exposure to high-temperature environments, even at temperatures exceeding 200°C, and can exhibit stable electret performance in applications with harsh temperature environments.

[0042] The specific structural example of the electret 1 will be described in detail below. The electret 1 has any external shape corresponding to the shape of the substrate 10. The shape of the substrate 10 is, for example, a rectangular plate or a disk. Multiple thin films, which are called electret layers 2, are sequentially stacked on one side of the substrate 10 in the thickness direction X (here, the vertical direction in the figure). That is, the outer layer film 3 and the inner layer film 4, which are multiple thin films, have the same shape as the substrate 10, and their stacking direction is consistent with the thickness direction X of the substrate 10. Hereinafter, the surface on the side where the electret layers 2 are stacked is designated as the upper surface 11, and the surface on the opposite side is designated as the lower surface 12.

[0043] The first inorganic dielectric material that becomes the outer film 3 can be, for example, a composite oxide containing two different metal elements A and B as its basic composition. In this case, it is selected such that the band gap energy is 3 eV or higher, and that at least one of the metal elements A and B contains a trivalent metal element. Preferably, a material in which metal element A is a divalent or trivalent metal element and metal element B is a trivalent metal element is used.

[0044] As an example of such a first inorganic dielectric material, a composite oxide with a perovskite-type composition can be cited. That is, a first composite oxide containing two different trivalent metal elements A and B, represented by the formula ABO3, can be used as its basic composition. A representative composite oxide with a perovskite-type composition is one with a perovskite-type crystal structure possessing a cubic crystal system, where metal element A (A site) is located at each vertex of the cubic crystal, metal element B (B site) is located at the center of the cubic crystal, and the oxygen atom O is coordinated to each metal element A and B in a regular octahedral configuration. In perovskite structures, non-stoichiometric compositions are often used due to the absence of oxygen atoms; in such cases, the formula ABO3 can be used. x (x≤3) means.

[0045] Here, the first composite oxide only needs to have a basic composition represented by the formula ABO3. It can be a crystal with a perovskite-type crystal structure or an amorphous substance. In either case, it is preferable that the ratio of the basic constituent metal elements A, B, and O, as a whole, is A:B:O = 1:1:3 or a relationship close to that. In this case, if the oxygen content in the first composite oxide is less than the stoichiometric ratio of the basic composition, defects are more likely to be introduced, and the surface potential is more likely to increase.

[0046] In the electret layer 2, the morphology of the outer film 3, which is mainly composed of the first inorganic dielectric material, is not particularly limited. For example, it can be made into a film of the first composite oxide with an amorphous structure (hereinafter referred to as an amorphous film) or a film of the first composite oxide containing a crystalline structure (hereinafter referred to as an oxide crystalline film). In this case, it is not necessary for the outer film 3 to be an oxide with a uniform composition, and it can also be a composition that is partially different from the basic composition.

[0047] In this embodiment, the electret layer 2, in which an amorphous film is used as the outer film 3, will be described primarily. Compared to perovskite-structured oxide crystalline films of the same composition, amorphous films are more prone to forming defects due to dangling bonds in an unbonded state. In the electret layer 2, the presence of defects is considered important for the manifestation of the surface potential in the outer film 3; by using an amorphous film, a higher surface potential can be obtained. Furthermore, since amorphous films can be formed at lower temperatures than oxide crystalline films, thermal damage to wiring and the like can be suppressed during device fabrication.

[0048] The first composite oxide, preferably a first inorganic dielectric material, has a composition where metal element A is selected from at least one rare earth element R and metal element B is Al in the formula ABO3. The perovskite-type composite oxide (RAlO3; rare earth aluminate) obtained by combining trivalent rare earth element R with trivalent Al achieves a high surface potential due to its relatively large band gap energy (e.g., 4 eV or higher) and relatively small relative permittivity (e.g., 100 or lower). Furthermore, it can be manufactured using relatively inexpensive materials, which is advantageous in terms of manufacturing cost.

[0049] The rare earth element R, as a trivalent element, can be selected from at least one element chosen from Y, Sc, and the lanthanides. Examples of lanthanides include La, Pr, Nd, Sm, and Gd. Preferably, LaAlO3 (lanthanum aluminate), which contains La and Al as trivalent rare earth elements R, can be used.

[0050] The first composite oxide can also be a composition consisting of a portion of metal element A, a portion of metal element B, or both of these elements replaced by a dopant element D composed of different metal elements in the ABO3 formula. In this case, if the dopant element D is a metal element with a lower valence than metal elements A and B, defects due to oxygen imaginary sites are more likely to occur in the structure. For example, if metal element A is a trivalent rare earth element R, a divalent alkaline earth metal element is preferred; if metal element B is trivalent Al, one or more elements selected from divalent alkaline earth metal elements and Zn are preferred. Examples of alkaline earth metal elements include Mg, Ca, Sr, and Ba.

[0051] The combination of metal elements A and B with dopant element D is not particularly restricted. By replacing the metals with a lower valence dopant element D, defects caused by oxygen deficiency occur in the perovskite composition to maintain electroneutrality, which helps to increase the surface potential. Since there is a correlation between the amount of dopant element D replacement and the amount of defects, the amount of defects affecting the surface potential can be controlled by adjusting the amount of dopant element D introduced, thus obtaining stable surface potential characteristics.

[0052] Specifically, a representative example of rare-earth aluminates is lanthanum aluminate (LaAlO3), which can be structured by replacing a portion of La with an alkaline earth metal element (such as Ca). In this case, considering the substitution amount of the dopant element D and the oxygen content that varies due to the atmosphere, etc., the composition (La,Ca)AlO3 can be used. x (x<3) indicates this. Alternatively, for simplicity, the basic compositional formula before substitution can be used. Furthermore, for example, when considering only the dopant element D, if the substitution ratio is set to Y (atm%), the compositional formula can be expressed as La. (1-Y) Ca Y AlO 3-Y / 2 .

[0053] The substitution ratio of dopant element D, where metal element A is replaced, is preferably 20 atm% or less, and more preferably set within a range of 0.5 atm% to 20 atm%. Similarly, the substitution ratio of dopant element D, where metal element B is replaced, is preferably 20 atm% or less, and more preferably set within a range of 0.5 atm% to 20 atm. When the substitution ratio is set to 0.5 atm% or more, an increase in surface potential is obtained compared to the case where no dopant element D is introduced. However, if the substitution ratio is close to 20 atm%, the effect of introducing dopant element D tends to decrease. The reason for this may not be clear, but it is speculated that a larger relative permittivity plays a role in suppressing the increase in surface potential. Therefore, it is preferable to set the substitution ratio appropriately within a range not exceeding 20 atm% in order to obtain the desired characteristics.

[0054] Preferably, the relative permittivity of the first inorganic dielectric material, which is the main component of the outer film 3, is greater than that of the second inorganic dielectric material, which is the main component of the inner film 4, in the electret layer 2. The relative permittivity of the first inorganic dielectric material can be adjusted, for example, by the combination of metal elements A and B, the dopant element D introduced into metal elements A and B, and its substitution ratio. Furthermore, the relative permittivity is an inherent value expressed as the ratio of the permittivity of each material to the permittivity of vacuum (i.e., relative permittivity = permittivity ε / permittivity of vacuum ε0).

[0055] In the electret layer 2, the outer film 3 forming its outer surface can be considered to exhibit a high surface potential, and the inner film 4 is located between the outer film 3 and the substrate 10, thereby achieving a high charge accumulation effect at the layer interface and stabilizing the surface potential. In this case, the outer film 3 is made of a material with a relatively high permittivity, which helps to increase the amount of charge brought about by the charging process, while the inner film 4 is made of a material with a relatively low permittivity, thereby suppressing charge movement and helping to stabilize the charge accumulated at the interface.

[0056] This structure suppresses the outflow of charge accumulated in the electret layer 2 through the substrate 10, maintaining the surface potential exhibited by the charging process even at high temperatures. The relative permittivity of the first inorganic dielectric material is not particularly limited, but it is preferable to have a relative permittivity of 10 or higher to obtain a higher surface potential (e.g., an absolute value of 1000 V or higher). The upper limit of the relative permittivity is not particularly limited, but it is preferable to have, for example, around 100 or less. The desired surface potential can be obtained by selecting the first inorganic dielectric material in combination with the bandgap energy.

[0057] The second inorganic dielectric material is not particularly limited and can be appropriately selected from inorganic dielectric materials with a smaller relative permittivity compared to the first inorganic dielectric material. Preferably, it is an inorganic compound with a relative permittivity of around 10 or less. Examples of such inorganic compounds include oxides, nitrides, oxynitrides, or mixtures thereof containing metallic elements such as Si or Al. Preferably, Si compounds such as SiO2 and SiN, and AlO2 are also suitable examples. x Al compounds such as Al2O3 (e.g., Al2O3) or mixtures of two or more of these compounds may be appropriately selected, taking into account the first inorganic dielectric material, the material of the substrate 10, the film formation method on the substrate 10, etc.

[0058] The material of the substrate 10 is not particularly limited; for example, conductive Si can be used. In addition, conductive substrates using conductive materials such as (Nb,Sr)TiO3 and metals, or insulating substrates using insulating materials such as Al2O3 and glass can also be used.

[0059] As in Figure 2 In one example shown in the above figure, in the electret layer 2, the first inorganic dielectric material constituting the outer film 3 can be set to have the composition (La, Ca)AlO. x The first composite oxide (x<3) is SiO2, which constitutes the second inorganic dielectric material of the inner layer film 4. The inorganic dielectric film 20, which combines the outer layer film 3 and the inner layer film 4, is formed, for example, directly on the upper surface 11 of the substrate 10 made of conductive Si, and electretized to form an electret 1 with an overall 3-layer structure.

[0060] As in Figure 2 In the modified example shown in the figure below, the electret layer 2 can also be made into a multilayer structure with two or more inner layers 4. A multilayer film (hereinafter referred to as a multilayer film) can also be constructed in this way. In this case, two or more of the various metal compounds exemplified as the second inorganic dielectric material can be arbitrarily combined. Here, the inner layer film 4 is configured as a multilayer film having a first layer 4a (e.g., SiO2) and a second layer 4b (e.g., SiN) in contact with the upper surface 11 of the substrate 10.

[0061] The method for forming the inorganic dielectric film 20 is not particularly limited, and any method can be used. Specifically, examples include physical vapor deposition (PVD) such as thermal oxidation and sputtering, chemical vapor deposition (CVD), fusion deposition, and sol-gel methods. The outer layer 3 and inner layer 4 constituting the inorganic dielectric film 20 can be selected based on the desired film quality and thickness.

[0062] For example, when sputtering is used as the film formation method for the outer layer film 3 and the inner layer film 4, crystals of the first and second inorganic dielectric materials with the same composition as the film to be formed are used as targets. A high voltage is applied in an inert gas, thereby causing accelerated ions to collide with the targets and forming a thin film of the desired composition on the upper surface of the substrate 10. Furthermore, as... Figure 2 As shown, when the second inorganic dielectric material constituting the inner layer film 4 contains SiO2, a thermal oxidation film of SiO2 can be formed on the surface of the Si substrate 10 using a thermal oxidation method.

[0063] The film-forming temperature can generally be set to a temperature corresponding to the material within the range of room temperature to 1000°C. By performing film formation at temperatures below 1000°C using this method, it is possible to form thin films of the first and second inorganic dielectric materials that become the inorganic dielectric film 20 while suppressing damage caused by high temperatures to the substrate 10 or wiring on the substrate 10. Furthermore, the first and second inorganic dielectric materials that become the target raw materials can be materials manufactured using high-temperature processes exceeding 1000°C.

[0064] The thin film formed on the substrate 10 can be made to have any thickness, for example, 0.01 μm or more, by adjusting the film formation conditions. Preferably, by making the inorganic dielectric film 20 a thin film in the range of 0.1 μm to 10 μm, it is possible to make an electret 1 suitable for use in small devices such as vibration power generation elements and memory circuits. In this case, the surface potential of the electret layer 2 is positively correlated with the thickness of the inner layer film 4, exhibiting the characteristic that the thicker the inner layer film 4, the higher the surface potential. The thickness of the inner layer film 4 is preferably adjusted to be 0.1 μm or more, more preferably 0.5 μm or more, to obtain the desired characteristics.

[0065] On the other hand, the surface potential of the electret layer 2 is independent of the thickness of the outer layer 3, and a substantially constant surface potential is achieved by sandwiching the inner layer 4 between it and the substrate 10. Therefore, the thickness of the outer layer 3 only needs to be 0.01 μm or more, preferably 0.1 μm or more, so that a surface potential corresponding to the composition, charging conditions, etc., can be stably achieved. More preferably, the thickness of the outer layer 3 is adjusted to a sufficient thickness in the range of 0.5 μm or more, such that insulation breakdown does not occur relative to the applied voltage during charging.

[0066] The electret 1 can be obtained by performing an electrification process in the lamination direction (i.e., the thickness direction X) while an inorganic dielectric film 20 is deposited on the upper surface 11 of the substrate 10. The electrification process is not particularly limited; for example, a method such as applying a voltage between the ground electrode and the counter electrode connected to the inorganic dielectric film 20 under heating conditions using corona discharge can be employed. Alternatively, an electrification process can be performed by applying a high voltage at high temperature.

[0067] Furthermore, since the surface potential is proportional to the voltage applied to the inorganic dielectric film 20 formed on the substrate 10, it is sufficient to apply the required voltage to achieve the surface potential required for the application. Alternatively, for the required voltage, the film thickness can be increased accordingly to prevent insulation failure.

[0068] (Implementation Method 2)

[0069] Next, Embodiment 2 of the electret will be described. The basic structure of the electret 1 in this embodiment is the same as that in Embodiment 1, and has... Figure 1 The substrate 10 and the electret layer 2 formed on its surface are shown. The electret layer 2 has a double-layer structure having an outer layer 3 and an inner layer 4. In this embodiment, the first inorganic dielectric material, which is the main component of the outer layer 3, is changed. Hereinafter, the differences will be described in detail. In addition, unless otherwise specified, any reference numerals used in Embodiment 2 and thereafter that are the same as those used in the previously described embodiments indicate the same constituent elements as in the previously described embodiments.

[0070] The outer film 3 constituting the electret layer 2 has the same morphology as in Embodiment 1, and can be made into an amorphous film or an oxide crystalline film with the first inorganic dielectric material as the main component. The material of the substrate 10, the second inorganic dielectric material constituting the inner film 4, the film formation method, the film thickness, and other aspects can also be the same as in Embodiment 1.

[0071] In this embodiment, the first inorganic dielectric material is also based on a composite oxide with a band gap energy of 3 eV or higher and at least one of the metal elements A and B being a trivalent metal element. Preferably, a material composed of a divalent or trivalent metal element A and a trivalent metal element B is used. As such a composite oxide, a second composite oxide having a garnet-type composition or a third composite oxide having a spinel-type composition can be used instead of the perovskite-type composite oxide of Embodiment 1.

[0072] The first inorganic dielectric material can contain two different trivalent metal elements A and B, and have the composition formula A3B5O. 12 The second composite oxide is represented as the basic composition. In this case, the second composite oxide can be either a crystal with a cubic garnet-type crystal structure or an amorphous substance. In either case, it is preferable that the ratio of the metal elements A, B, and O, which are the basic constituent elements, as a whole, is A:B:O = 3:5:12 or a relationship close to this.

[0073] In the second composite oxide, the combination of trivalent metal elements A and B is not particularly limited. Preferably, similar to the first composite oxide with a perovskite composition, it can be configured with the formula A3B5O. 12In this composition, metal element A is at least one element selected from rare earth element R, and metal element B is Al. The trivalent rare earth element R is, for example, at least one element selected from Y, Sc, and lanthanides. Examples of lanthanides include La, Pr, Nd, Sm, and Gd. Specifically, a second composite oxide having such a composition can be Y3Al5O, containing Y as a trivalent rare earth element R and Al. 12 wait.

[0074] In the composition formula A3B5O 12 In this context, metal element A can be a combination of two or more rare earth elements. Furthermore, metal element B can be a combination of Al with at least one element selected from typical trivalent elements (e.g., Ga). Specifically, a second composite oxide with such a composition can be exemplified by Gd3(Al,Ga)5O, containing Gd and Al as trivalent rare earth elements R and Ga. 12 wait.

[0075] Furthermore, in the composition formula A3B5O 12 The composition can also be a part of metal element A or a part of metal element B, or a composition in which both are replaced by dopant element D composed of different metal elements. In this case, dopant element D is preferably a metal element with a lower valence than metal elements A and B. For example, if metal element A is a trivalent rare earth element R, a divalent alkaline earth metal element is preferred; if metal element B is trivalent Al, one or more elements selected from divalent alkaline earth metal elements and Zn are preferred. Examples of alkaline earth metal elements include Mg, Ca, Sr, and Ba.

[0076] The substitution ratio of dopant element D, in which metal elements A and B are replaced, can be appropriately set, for example, below 20 atm%, preferably within a range of 0.1 atm% to 20 atm%. More preferably, if the substitution ratio is set to 0.5 atm%, defects are easily introduced, contributing to the increase in surface potential. The same applies to metal element B; it is preferable to appropriately set the substitution ratio within a range not exceeding 20 atm% to obtain the desired properties.

[0077] Furthermore, the first inorganic dielectric material can be based on a third composite oxide containing divalent metal element A and trivalent metal element B, represented by the formula AB₂O₄. In this case, the third composite oxide can be either a crystal with a spinel-type crystal structure having a cubic crystal system, or an amorphous material. In either case, it is preferable that the ratio of the metal elements A, B, and O as basic constituent elements, as a whole, is A:B:O = 1:2:4 or a relationship close to that.

[0078] In the third composite oxide, the combination of divalent metal element A and trivalent metal element B is not particularly limited. Preferably, the divalent metal element A in the formula AB₂O₄ is at least one element selected from alkaline earth metal elements and transition metal elements, and the trivalent metal element B is Al. Examples of alkaline earth metal elements include Mg, Ca, Sr, and Ba. Examples of transition metal elements include Fe, Zn, and Mn.

[0079] As third composite oxides with such a composition, in addition to MgAl2O4 (spinel), SrAl2O4, FeAl2O4, ZnAl2O4, MnAl2O4, etc. can also be mentioned, all of which have relatively high band gap energies (e.g., above 4 eV).

[0080] In this embodiment, the inorganic dielectric film 20 also includes an outer layer film 3 and an inner layer film 4, both using the second and third composite oxides as the first inorganic dielectric material. The outer layer film 3 does not need to be an oxide with a uniform composition; for example, it can partially have a different composition from the second and third composite oxides, which are the basic components. The electret layer 2 is obtained by subjecting the inorganic dielectric film 20 to an electrical charge treatment. The electrical charge treatment method can be the same as described in Embodiment 1.

[0081] Similar to the first composite oxide, the second and third composite oxides can also be configured such that, due to oxygen deficiency or other defects in their structure, the oxygen content is relatively low compared to the basic composition. In this case, they can be configured as A3B5O. x (x≤12), composition formula AB2O x (x≤4) can be represented as such. Alternatively, for simplicity, let's assume it is represented using the basic compositional formula before the substitution.

[0082] Specifically, for example, in Y3Al5O, which is the second composite oxide 12 In this case, a structure can be made in which a portion of Y is replaced by an alkaline earth metal element (e.g., Mg) as a dopant element D. Considering the amount of dopant element D replaced and the oxygen content varying due to the atmosphere, etc., the composition (Y, Mg)3Al5O is used. x(x<12) represents this. Alternatively, for simplicity, let's assume it's represented using the basic compositional formula before the substitution.

[0083] At this moment, as if Figure 3 As illustrated in the example, the electret layer 2 can, for instance, have a first inorganic dielectric material constituting the outer film 3 composed of the formula (Y,Mg)3Al5O x (x<12) represents the second composite oxide, and the second inorganic dielectric material constituting the inner layer film 4 is SiO2. The inorganic dielectric film 20, which combines the outer layer film 3 and the inner layer film 4, is formed directly on the upper surface 11 of the substrate 10 made of conductive Si, and is electretized to form an electret 1 with an overall 3-layer structure.

[0084] In the second and third composite oxides, which serve as the first inorganic dielectric material in this embodiment, the molar fraction of metal element B in the total amount of metal elements A and B becomes larger than that in the first composite oxide. That is, for the first composite oxide composed of perovskite type used in the first embodiment 1, metal elements A and B are in equal ratio (A:B = 1:1), while for the second composite oxide composed of garnet type, A:B = 3:5, and for the third composite oxide composed of spinel type, A:B = 1:2, the proportion of metal element B becomes greater.

[0085] The first inorganic dielectric material contains first to third composite oxides, which are composed of metal elements A, B, and O as basic constituent elements, in a predetermined ratio of A:B:O. These first to third composite oxides, through combinations of different metal elements A and B and the introduction of dopant element D, exhibit desired characteristics higher than those of the second inorganic dielectric material, with a band gap energy of 3 eV or higher and a relative permittivity of 100 or lower. Furthermore, the inorganic dielectric film 20, which combines the first and second inorganic dielectric materials, exhibits a high surface potential through electret formation and can stably maintain the exhibited surface potential.

[0086] [Example]

[0087] (Example 1)

[0088] Make using the following methods Figure 2 The electret 1 in Embodiment 1 shown in the upper figure is an example of an embodiment. A first composite oxide composed of a perovskite type is used as the first inorganic dielectric material.

[0089] <Formation of Inorganic Dielectric Film 20>

[0090] First, an inner layer film 4, composed of a thin film of a second inorganic dielectric material, is formed by thermally oxidizing the upper surface 11 of a substrate 10 made of conductive Si to create a thermally oxidized film (SiO2). The substrate 10 has a thickness of 625 μm, and the inner layer film 4 has a thickness of 1.2 μm. Next, an outer layer film 3, composed of a first inorganic dielectric material, is formed on the upper surface of the inner layer film 4 by sputtering. The sputtering conditions are set at 360°C in an Ar atmosphere, and a crystal with the same composition as the first composite oxide used as the first inorganic dielectric material is used as the target. The amorphous film that will become the outer layer film 3 is formed with a thickness of 1.3 μm.

[0091] The first composite oxide is a lanthanum aluminate (LaAlO3; hereinafter referred to as LAO) composite oxide containing La and Al as metal elements A and B in the composition ABO3, and a portion of La is replaced by dopant element D. Here, Ca is used as the dopant element D, and its replacement ratio is set to 1 atm% (hereinafter, appropriately referred to as LAO with 1% Ca). Furthermore, as a target, a polycrystalline [(LaAlO3)] containing 1 atm% Ca, formed into a specified shape and sintered, is prepared in advance. 0.99 Ca 0.01 AlO x In this way, an amorphous film containing Ca, La, Al, and O with a La:Al:O ratio of approximately 1:1:3 is obtained.

[0092] Furthermore, LAO-based composite oxides exhibit approximately the same bandgap energy as lanthanum aluminate (LaAlO3), a representative composition with a bandgap energy of 5.6 eV, and in structures formed by replacing a portion of La with Ca as a dopant element D. In addition, the relative permittivity of LAO-based composite oxides (the first inorganic dielectric material) is approximately 22, which is greater than that of SiO2 (the second inorganic dielectric material), which has a relative permittivity of 3.8.

[0093] <Electroporation>

[0094] Thus, a sample with an inorganic dielectric film 20 deposited on the substrate 10 was prepared, and then an electret 1 with an electret layer 2 was formed by performing an electret treatment (Example 1). The electret treatment used corona discharge, with the substrate 10, which is connected to the inner layer 4 of the inorganic dielectric film 20, serving as a ground electrode. A discharge needle, acting as a corona discharge electrode, was positioned opposite the outer layer 3 side, and corona discharge was generated by applying a negative voltage. The sample was then placed on a heater plate, with the lower surface 12 of the substrate 10 connected to the grounded heater plate. The heating temperature of the heater plate and the conditions for the electret treatment performed by corona discharge were set as follows: Heating temperature: 200°C; Discharge needle voltage: -10kV; Discharge time: 15 seconds; Distance between the discharge needle and the sample: 20mm.

[0095] <Surface Potential Measurement>

[0096] Thus, ions charged by corona discharge collide with the exposed surface of the inorganic dielectric film 20 formed on the substrate 10 (i.e., the surface of the outer film 3), and are electretted by acquiring a negative charge. Next, the surface potential of the resulting electret 1 (Example 1) was measured. In the measurement, a surface potentiometer (MODEL341-B: manufactured by TREK) was used, with the measuring probe positioned opposite the electret 1 resting on the worktable, to measure the surface potential non-contactly. Multiple samples with the same structure (sample number n=2) were prepared, charged, and then heated at 200°C for 30 minutes. The surface potential after the heating treatment was measured, and all yielded a relatively high surface potential exceeding 1100V (absolute value).

[0097] (Comparative Example 1)

[0098] For comparison, such as Figure 4 As shown in the upper figure, an electret 1 was fabricated using a single-layer inorganic dielectric film 21. The inorganic dielectric film 21, which serves as the electret layer 2, is configured as a film structure with the same inorganic dielectric material as the outer film 3 as the main component, i.e., a single-layer film without the inner film 4 in the structure of Example 1. Otherwise, it is the same as in Example 1. Specifically, an amorphous film containing 1 atm% Ca and a LAO-based composite oxide was directly sputtered onto the upper surface 11 of a substrate 10 made of conductive Si. After forming the inorganic dielectric film 21, it was also charged to form the electret 1. Furthermore, the thickness of the substrate 10 was set to 625 μm, and the thickness of the inorganic dielectric film 21 was set to 1.3 μm.

[0099] For electret 1 of Comparative Example 1, the surface potential immediately after electret treatment was measured using the same method as in Example 1. In this case, after electretization by electret treatment, the surface potential was measured immediately after heating at 100°C for 30 minutes, and then after heating at 200°C for 30 minutes, to evaluate the effects of the thermal environment and the passage of time. Figure 4 In the figure below, the results are represented as immediately after being charged, after heating at 100℃ (30 min), and after heating at 200℃ (30 min).

[0100] exist Figure 4In the figure below, the surface potential immediately after charging is approximately 400V (absolute value), which is less than half of the surface potential in Example 1. Furthermore, after heating at 100°C, it exceeds 200V (absolute value), halving from the surface potential immediately after charging; after heating at 200°C, the surface potential decreases further significantly, almost disappearing. As described above, it is confirmed that in a structure where the electret layer 2 formed on the substrate 10 is composed of a single-layer inorganic dielectric film 21, maintaining the surface potential at high temperatures is difficult.

[0101] (Examples 2-5)

[0102] Next, in the same electret layer 2 film structure as in Example 1, an electret 1 with a modified inner layer film 4 thickness was fabricated. Specifically, thermal oxide films (SiO2) as inner layer film 4 were formed on the upper surface 11 of substrate 10 (conductive Si) with thicknesses of 0.1 μm, 0.3 μm, 0.5 μm, and 1.0 μm, respectively. Then, an amorphous film (LAO with 1% Ca added) as outer layer film 3 was formed by sputtering to create an inorganic dielectric film 20. Then, the electret 1 of Examples 2 to 5 was formed by charging in the same manner as in Example 1. Assuming the thickness of substrate 10 is 625 μm and the thickness of outer layer film 3 is set to 1.3 μm.

[0103] For electret 1 in Examples 2-5, the surface potential was measured using the same method as in Example 1. In this case, multiple samples (n=2) were prepared for each example, and after charging, they were heated at 200°C for 30 minutes, and the surface potential after the heat treatment was measured. Furthermore, for electret 1 in Example 1, the surface potential after heating at 200°C for 30 minutes was also measured, and these results were compared and displayed. Figure 5 .

[0104] exist Figure 5 In the figure, the horizontal axis represents the thickness of the inner layer film 4 (SiO2), and the results of Comparative Example 1 without the inner layer film 4 are also shown. That is, when the thickness of the inner layer film 4 is 0 μm, the surface potential is 0 V. In contrast, in Examples 1 to 5 with the inner layer film 4, a surface potential (absolute value) of about 140 V was obtained with a thickness of 0.1 μm (Example 2), and the surface potential increased proportionally to the thickness of the film. Specifically, a relatively high surface potential of about 400 V was obtained with a thickness of 0.3 μm (Example 3), about 600 V with a thickness of 0.5 μm (Example 4), and about 1000 V with a thickness of 1.0 μm (Example 5).

[0105] In addition, Figure 6The diagram shows the change in surface potential of each sample of electret 1 from Examples 1 to 5 after heat treatment and subsequent placement at room temperature. The surface potential of the heat-treated sample was set as the surface potential at the start of the test (time elapsed: 0), and the change was investigated until a predetermined time (e.g., approximately 5 to 10 minutes) had elapsed. Figure 6 As shown, almost no change in surface potential over time was observed in Examples 1-5.

[0106] according to Figure 5 , Figure 6 As a result, when the electret layer 2 has a film structure with an outer film 3 and an inner film 4 (Examples 1-5), the surface potential is maintained even after heat treatment at 200°C, and the disappearance of the surface potential as observed in Comparative Example 1 is not observed. At this time, within the range of 0.1 μm (Example 2) to 1.2 μm (Example 1) film thickness of the inner film 4, the thicker the inner film 4, the higher the surface potential, and no change in surface potential is observed even after time has passed.

[0107] (Examples 6-7)

[0108] Next, electret 1, with a modified outer layer film 3 thickness, was fabricated in the electret layer 2 structure of Example 2. Specifically, a thermal oxide film (SiO2) as the inner layer film 4 was formed on the upper surface 11 of the substrate 10 (conductive Si), and then an amorphous film (LAO with 1% Ca added) as the outer layer film 3 was formed by sputtering to a thickness of approximately 0.4 μm, forming an inorganic dielectric film 20. Then, an electrical charging process was performed to form electret 1 of Example 6. In addition, except that the outer layer film 3 was formed to a thickness of approximately 0.9 μm, the inorganic dielectric film 20 was similarly formed and subjected to an electrical charging process to form electret 1 of Example 7.

[0109] For the electret 1 of Examples 6 and 7, after charging and heating at 200°C for 30 minutes, the surface potential was measured using the same method as in Example 1. The results were compared with those of Example 2 and displayed together. Figure 7 .

[0110] exist Figure 7 In Examples 6 and 7, the surface potential (absolute value) is approximately 140V, which is comparable to the result in Example 2. Thus, the magnitude of the surface potential is independent of the thickness of the outer layer 3; the same result is obtained as long as the first inorganic dielectric material of the outer layer 3 is the same. Furthermore, as... Figure 5 , Figure 6As in Examples 1 to 5, the magnitude of the surface potential is positively correlated with the thickness of the inner layer film 4, and thermal stability and time-stability can be obtained at any film thickness.

[0111] exist Figure 8 The text indicates the results obtained by storing the electret 1 structure of Example 5 for an extended period and investigating the changes in surface potential over time. Specifically, multiple samples with the same structure (n=3 samples) were prepared, charged, heated at 200°C for 30 minutes, and their surface potentials were measured. These samples were then stored in the atmosphere for a specified period, and their surface potentials were measured again. The surface potentials of each sample were measured at the same time points within a period up to approximately 2700 minutes.

[0112] exist Figure 8 In Example 5, the surface potential (absolute value) of any sample immediately after heat treatment was approximately 1000V. Then, over time, the surface potential gradually decreased (e.g., during the period up to 500 minutes), the decrease was slight, and thereafter almost no further decrease in surface potential was observed.

[0113] Based on these results, it can be seen that the electret 1 exhibits a surface potential corresponding to the combination of the outer film 3 and the inner film 4 constituting the electret layer 2 and the film thickness of the inner film 4, which can suppress the effects caused by temperature environment and long-term storage, and exert thermal stability and time stability characteristics.

[0114] (Examples 9-10)

[0115] Next, an electret 1, in which the second inorganic dielectric material constituting the inner layer film 4 was changed in the structure of electret layer 2 of Example 1, was fabricated, and its thermal stability and stability over time were investigated. Specifically, a thin film composed of SiN was formed on the upper surface 11 of the substrate 10 (conductive Si) as the inner layer film 4 by plasma CVD. For the film formation by plasma CVD, SiH4 and NH3 were used as raw material gases, and the substrate temperature was set to 300°C to form a CVD thin film composed of SiN with a film thickness of 0.3 μm.

[0116] On the upper surface of the inner layer film 4, an amorphous film (LAO with 1% Ca added) that will become the outer layer film 3 is formed by sputtering to a thickness of 1.3 μm, thus forming an inorganic dielectric film 20. Then, an electret 1 of Example 9 is formed by charging in the same manner as in Example 1. In addition, except for forming a 0.5 μm CVD thin film made of SiN as the inner layer film 4, the electret 1 of Example 10 is also formed in the same manner.

[0117] For electret 1 in Examples 9 and 10, the surface potential was measured using the same method as in Example 1. This time, multiple samples with the same structure (n = 2 samples) were prepared, and after being charged, their surface potentials were measured after heating at 200°C for 30 minutes. The results are expressed as follows: Figure 9 middle.

[0118] exist Figure 9 In the middle, the relationship between the thickness of the inner layer 4 and the surface potential is also... Figure 5 The relationship shown is the same; it can be seen that as the thickness of the inner layer film 4 increases from 0.3 μm (Example 9) to 0.5 μm (Example 10), the surface potential (absolute value) tends to increase from around 125 V to over 210 V. This confirms that regardless of the type of the second inorganic dielectric material used as the inner layer film 4, the thermal stability is improved, exhibiting a stable surface potential that is positively correlated with the thickness of the inner layer film 4.

[0119] In addition, Figure 10 The diagram illustrates the change in surface potential of each electret 1 sample from Examples 9-10 after heat treatment, when placed at room temperature. The surface potential of the heat-treated sample was set as the surface potential at the start of the test (after time: 0), and the change was investigated until a predetermined time (e.g., approximately 5 to 10 minutes) elapsed. Figure 10 In Examples 9 and 10, almost no change in surface potential due to the passage of time was observed.

[0120] (Example 11)

[0121] Next, the following method was used to create... Figure 3 The electret 1 of Embodiment 2 shown uses a second composite oxide composed of garnet as the first inorganic dielectric material.

[0122] First, similar to Example 1, an inner layer film 4 is formed by thermally oxidizing the upper surface 11 of the substrate 10 (conductive Si) to create a thermally oxidized film (SiO2) of the second inorganic dielectric material. The thickness of the substrate 10 is 625 μm, and the thickness of the inner layer film 4 is set to 1.2 μm. Next, an outer layer film 3 composed of the first inorganic dielectric material is formed on the upper surface of the inner layer film 4 by sputtering. The sputtering conditions are set to 360°C and an Ar atmosphere. Using a crystal with the same composition as the second composite oxide that serves as the first inorganic dielectric material as the target, an amorphous film, which will become the outer layer film 3, is formed with a film thickness of 0.6 μm to create an inorganic dielectric film 20. Then, an electret 1 of Example 11 is formed by charging.

[0123] The second composite oxide is defined as having the composition A3B5O, containing Y and Al as garnet type. 12The metal elements A and B in Y are replaced by a portion of Y with dopant element D to obtain Y3Al5O. 12 (Hereinafter referred to as YAG)-based composite oxides. Here, Mg is used as the dopant element D, and its substitution ratio is set to 4 atm% (hereinafter, appropriately referred to as YAG with 4% Mg added). Furthermore, as a target, a polycrystalline YAG-based composite oxide containing 4 atm% Mg is prepared in advance [(Y 2.88 Mg 0.12 Al5O x In this way, an amorphous film containing Mg, Y, Al, and O with a Y:Al:O ratio of approximately 3:5:12 is obtained.

[0124] In addition, Y3Al5O, a representative composition of YAG-based composite oxides, is... 12 The band gap energy is approximately 5 eV, and it has a roughly equivalent band gap energy even in structures obtained by replacing a portion of Y with Mg as a dopant element D. Furthermore, the relative permittivity of the YAG-based composite oxide (the first inorganic dielectric material) is approximately 12, which is greater than that of SiO2 (the second inorganic dielectric material), which has a relative permittivity of 3.8.

[0125] For electret 1 in Example 11, the surface potential was measured using the same method as in Example 1. Multiple samples with the same structure (n=3 samples) were prepared, charged, and then heated at 200°C for 30 minutes. The surface potential after the heat treatment was measured. As a result, a relatively high surface potential (absolute value) of approximately 900V to 1200V was obtained.

[0126] (Examples 12-14)

[0127] Furthermore, for the electret 1 of Example 11, the thickness of the inner layer film 4 was changed to 0.3 μm, 0.5 μm, and 1.0 μm. Otherwise, the inorganic dielectric film 20 was similarly formed and subjected to charging treatment to produce the electrets 1 of Examples 12-14. For these electret 1 samples of Examples 12-14 (sample number n = 1-3), the surface potential was measured after charging treatment and heating at 200°C for 30 minutes, using the same method as in Example 1. Their results are presented together with the results of Example 11 and Comparative Example 1. Figure 11 middle.

[0128] exist Figure 11In Examples 12-14, the surface potentials (absolute values) were approximately 400V, 600V, and 800V, respectively, indicating improved thermal stability compared to Comparative Example 1. Furthermore, based on the results of Examples 11-14, it was found that the surface potential was positively correlated with the thickness of the inner layer film 4, and this correlation was also observed when the second composite oxide was used as the first inorganic dielectric material. Figure 5 The same trend.

[0129] (Examples 15-16)

[0130] Next, electret 1, in which the second inorganic dielectric material constituting the inner layer film 4 was changed in the structure of electret layer 2 of Example 11, was fabricated, and its thermal stability and stability over time were investigated. Specifically, a thin film composed of SiN was formed as the inner layer film 4 on the upper surface 11 of the substrate 10 (conductive Si) by plasma CVD. Regarding the film formation by plasma CVD, SiH4 and NH3 were used as raw material gases, and the substrate temperature was set to 300°C to form a CVD thin film composed of SiN with a film thickness of 0.3 μm.

[0131] On the upper surface of the inner layer film 4, an amorphous film (YAG with 4% Mg added) that will become the outer layer film 3 is formed by sputtering to a thickness of 0.6 μm, thus forming an inorganic dielectric film 20. Then, it is charged in the same way as in Example 11 to form the electret 1 of Example 15. In addition, except for forming a 0.5 μm CVD thin film made of SiN as the inner layer film 4, the electret 1 of Example 16 is also formed in the same way.

[0132] For electret 1 in Examples 15-16, the surface potential was measured using the same method as in Example 1. This time, multiple samples with the same structure (n=2 samples) were prepared, and their surface potentials were measured after being charged and heated at 200°C for 30 minutes. The results are presented as follows: Figure 12 middle.

[0133] exist Figure 12 In the middle, the relationship between the thickness of the inner layer 4 and the surface potential is also... Figure 9 The relationship shown is the same; it can be observed that as the thickness of the inner layer film 4 increases from 0.3 μm (Example 15) to 0.5 μm (Example 16), the surface potential (absolute value) tends to increase from around 120V to over 200V. This confirms that regardless of the type of the second inorganic dielectric material used as the inner layer film 4, the thermal stability is improved, exhibiting a stable surface potential that is positively correlated with the thickness of the inner layer film 4.

[0134] Furthermore, for each sample of electret 1 in Examples 15-16, the change in surface potential after heat treatment and when placed at room temperature is expressed as follows: Figure 13 In this case, the surface potential of the heat-treated sample is set to the surface potential at the start of the test (after time: 0), and the change is investigated until a specified time (e.g., approximately 5 to 10 minutes) has elapsed. Figure 13 In Examples 15 and 16, almost no change in surface potential over time was observed.

[0135] (Examples 17-18)

[0136] Next, an electret 1 with a modified inner layer film 4 structure was fabricated in the electret layer 2 of Example 1, and its thermal stability and stability over time were investigated. The electret layer 2 has... Figure 2 The structure of Embodiment 1 shown in the lower figure has an inner membrane 4 configured as a multilayer membrane having a first layer 4a and a second layer 4b.

[0137] Specifically, a 1.2 μm thick thermal oxide film (SiO2) is formed on the upper surface 11 of the substrate 10 (conductive Si) through thermal oxidation, forming the first layer 4a of the inner layer film 4. Next, a 0.3 μm thick CVD film composed of SiN is formed by plasma CVD, forming the second layer 4b. On its upper surface, an amorphous film (LAO with 1% Ca added) that will become the outer layer film 3 is further formed by sputtering to a thickness of 1.3 μm, forming the inorganic dielectric film 20. Then, an electret 1 of Example 17 is formed by charging. Furthermore, an electret 1 of Example 18 is also formed using a 0.5 μm thick CVD film composed of SiN as the second layer 4b of the inner layer film 4.

[0138] For the electrets 1 of Examples 17 and 18, the surface potential was measured using the same method as in Example 1. Specifically, after charging and heating at 200°C for 30 minutes, the surface potential was measured periodically after being stored in the atmosphere, and the results of investigating changes within a period of more than 6 minutes were expressed as follows. Figure 14 In. Figure 14 In the middle, together they expressed Figure 6 Results of electret 1 in Example 1.

[0139] exist Figure 14 In Example 17, the surface potential of electret 1 was approximately 800V (absolute value), and in Example 18, the surface potential of electret 1 was approximately 900V (absolute value). Furthermore, no decrease in surface potential over time was observed in electrets 1 of Examples 17 and 18; after more than 6 minutes, the surface potential remained approximately constant, showing the same trend as in electret 1 of Example 1.

[0140] Thus, when the inner layer film 4 is a multilayer film combining various second inorganic dielectric materials, an electret layer 2 can be formed by further stacking an outer layer film 3 composed of a first inorganic dielectric material, thereby improving the thermal stability and time-dependent stability of the electret 1. Furthermore, the surface potential of the electret 1 depends on the combination of the first and second inorganic dielectric materials that form the inner layer film 4 and the outer layer film 3, and on the thickness of the inner layer film 4. Therefore, if the layer structures of the electret layers 2 are the same, the thicker the inner layer film 4, the higher the surface potential.

[0141] (Comparative Examples 2-3)

[0142] For comparison, such as Figure 15 As shown, the electret 1 is a multilayer film consisting only of a second inorganic dielectric material in the inorganic dielectric film 22, which serves as the electret layer 2. That is, it does not have an outer layer film 3 made of a first inorganic dielectric material; the inorganic dielectric film 22 has a first layer 22a in contact with the substrate 10 and a second layer 22b on its outer side. Specifically, the first layer 22a is formed by forming a 1.2 μm thick thermal oxide film (SiO2) on the upper surface 11 of the substrate 10 (conductive Si), and the second layer 22b is formed by forming a 0.3 μm thick CVD thin film made of SiN on its upper surface using plasma CVD. Then, an electret treatment is performed to form the electret 1 of Comparative Example 2. In addition, besides forming the second layer 22b with a film thickness of 0.5 μm, the inorganic dielectric film 22 was also formed and charged to form the electret 1 of Comparative Example 3.

[0143] For electret 1 in Comparative Examples 2 and 3, the surface potential was measured after charging treatment and heating at 200°C for 30 minutes, using the same method as in Example 1. Furthermore, the change in surface potential when placed at room temperature (e.g., for about 5 to 10 minutes) was investigated. The results are expressed as follows: Figure 16 In. Figure 16 In Comparative Examples 2 and 3, the electret 1 exhibited a relatively high surface potential of approximately 800V (Comparative Example 2) to 900V (Comparative Example 3) after approximately 1 to 2 minutes of charging treatment. However, a slow decrease was observed, and the surface potential continued to decrease. Therefore, in Comparative Example 2, the surface potential decreased to approximately 700V (absolute value) after approximately 6 minutes, and in Comparative Example 3, the surface potential became approximately 600V (absolute value) after approximately 10 minutes.

[0144] In addition, such as Figure 17As shown, when the surface potential of electret 1 in Comparative Example 3 was further measured, the surface potential dropped to about 200V (absolute value) after about 20 minutes. Furthermore, it was determined that although the rate of decrease became gradual thereafter, the surface potential dropped to approximately 0 after about 80 minutes.

[0145] Thus, even with a structure that stacks multiple different inorganic dielectric materials, in an electret 1 that does not have an outer film 3 composed of a first inorganic dielectric material, the decrease in surface potential cannot be suppressed, and it is difficult to ensure the long-term stability of the surface potential.

[0146] Figures 18-19 The graph shows the results of electret 1 from Examples 17-18 together with those from Comparative Examples 2-3. Figure 18 This is Example 17 and Figure 15 The graph comparing the results of Comparative Example 2 shows that the electret 1 of Example 17 maintained a surface potential of approximately 800V (absolute value) and remained largely constant. In contrast, the surface potential of the electret 1 of Comparative Example 2 decreased over time, resulting in a larger difference between the surface potentials of the two examples. Furthermore, in... Figure 19 The same is true in the comparison results. The electret 1 of Example 18 has a surface potential of about 900V (absolute value) and is basically constant. In contrast, the surface potential of the electret 1 of Comparative Example 3 decreases over time, and the difference between the surface potential of the electret 1 and that of Example 18 becomes larger.

[0147] In this way, the electret 1, through the electret layer 2 on the substrate 10, has an outer layer film 3 made of a first inorganic dielectric material and an inner layer film 4 made of a second inorganic dielectric material, thereby improving thermal stability and exhibiting a high surface potential even in high-temperature environments above 200°C. Furthermore, its stability over time is improved, enabling it to maintain a stable surface potential for extended periods. Such an electret 1 can be used, for example, in high-temperature processes including reflow soldering in the manufacturing process of power generation devices, increasing the freedom of process design and thus contributing to reduced manufacturing costs. Moreover, it not only suppresses performance degradation during the manufacturing process but also maintains stable performance even under harsh temperature environments during subsequent use.

[0148] Furthermore, in the embodiments described above, the case where the outer film 3 of the electret layer 2 is an amorphous film has been primarily explained. However, when an oxide crystalline film containing a composite oxide with a crystalline structure is formed, it can be either a polycrystalline film or a mixed film containing composite oxide particles in a heat-resistant base film. Additionally, the outer film 3 of the electret layer 2 can also be formed into a multilayer structure with two or more layers.

[0149] This invention is not limited to the various embodiments described, and can be applied to various embodiments without departing from its spirit.

Claims

1. An electret having a substrate and an electret layer formed on its surface, The electret layer is obtained by subjecting an inorganic dielectric film to an electrical charge, wherein the inorganic dielectric film comprises an outer layer and an inner layer laminated in the thickness direction of the substrate. The outer layer film is a film mainly composed of a first inorganic dielectric material, which is a composite metal compound containing two or more different metal elements, at least containing a trivalent metal element, and has a band gap energy of 3 eV or higher. The inner membrane is a membrane whose main component is a second inorganic dielectric material that is different from the first inorganic dielectric material.

2. The electret as described in claim 1, The first inorganic dielectric material is a material with a composite oxide containing two different metal elements A and B as its basic composition, wherein metal element A is a divalent or trivalent metal element and metal element B is a trivalent metal element.

3. The electret as described in claim 2, The composite oxide is the first composite oxide represented by the formula ABO3, with the formula A3B5O. 12 The second complex oxide represented by the formula AB2O4, or the third complex oxide represented by the formula AB2O4.

4. The electret as described in claim 3, In the first composite oxide and the second composite oxide, metal element A is at least one element selected from rare earth elements, and in the third composite oxide, metal element A is at least one element selected from alkaline earth metal elements and transition metal elements.

5. The electret as described in claim 4, In the first composite oxide, the second composite oxide, and the third composite oxide, the metal element B is Al.

6. The electret as described in any one of claims 1 to 5, The relative permittivity of the first inorganic dielectric material is greater than that of the second inorganic dielectric material.

7. The electret as described in claim 6, The second inorganic dielectric material is a mixture of one or more compounds selected from Si and Al compounds.

8. The electret as described in any one of claims 1 to 5, The surface potential of the electret layer is positively correlated with the thickness of the inner layer film.

9. The electret as described in claim 8, The thickness of the inner membrane is 0.1 μm or more.

10. The electret as described in any one of claims 1 to 5, The inner layer film is a film with one or more layers, and the outer layer film is an amorphous film of the composite metal compound or a crystalline film of the composite metal compound.